Financial Technology Innovation in Modernizing Zakat Payments in the Digital Era - Abdullah abdullah (Journal of Islamic Economy and Business (JIsEB), 2024)
In the modern era of digital technology, the modernization of zakat (Islamic alms) payments has become imperative. Financial technology (fintech) systems offer a viable alternative to enhance the implementation of zakat among Indonesian Muslims. This article explores the Islamic perspective on utilizing fintech for zakat payments. It asserts that the use of fintech for zakat payments represents a progressive ijtihad (independent reasoning) product, employing a qualitative method with data collected through library research. The study finds that, in addition to offering a more efficient solution for zakat payments, the integration of fintech also constitutes an advancement in the fiqh (Islamic jurisprudence) related to zakat. However, the implementation of fintech in zakat management faces several challenges and may sometimes lead to criminal issues. Therefore, it is crucial to ensure that the fintech solutions employed adhere to sharia principles, as derived from the teachings of the Quran and Hadith. The article concludes that the utilization of fintech in zakat administration has the potential to improve its effectiveness, transparency, and accessibility for all stakeholders, aligning with the noble purpose of zakat in promoting social and economic welfare.